COVID-19: Bewertung der Impfung und das Sicherheitsempfinden am Arbeitsplatz: Ein empirischer Kurzbericht - Lösch, Regina; Wischlitzki, Elisabeth; Pfleger, Elisabeth; Voss, Amanda Sophie (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2021)
Objective: The approval so far of three vaccines against COVID-19 and the recommendation of the Standing Committee on Vaccination on the participation of company doctors create good prerequisites for the desired comprehensive vaccination of the population. This requires a willingness on the part of employees to get vaccinated. The aim of this article is to generate information about the assessment of vaccination and the associated perception in the workplace setting. As the risk of severe disease progression increases with age, the focus is on a consideration of older people. Methods: The cross-sectional survey was conducted as an online questionnaire using the LimeSurvey tool at the end of 2020. Employed persons aged 18 years and older were surveyed. The subsequent data analysis using IBM SPSS 21® software was both descriptive and inferential (ANOVA). Results: Almost one in two respondents (n=199) reported concern about becoming infected with COVID-19 and that they would feel safer at work if most of the population were vaccinated. 45.3% reported feeling more optimistic about the current situation because of the prospect of a vaccine, and 33.3% said that this made it easier to comply with contact restriction rules and recommendations. Inferential statistics show that older individuals (≥50 years) do not differ significantly from middle-aged (35-49 years) or younger individuals (≤34 years). Persons working from home estimate the risk of becoming infected to be significantly lower than persons in the office. Conclusion: The vaccination of a majority of the population - as well as working from home - would increase employees' perception of safety in the workplace. Vaccinations in a workplace setting offer a great opportunity to support the federal government's vaccination strategy.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Coronavirus; COVID-19; prevention; vaccination; workplace